Peningkatan Efisiensi Sel Surya Berbasis Titania Melalui Penyisipan Logam Besi pada Lapisan Aktif Titania - Rita Prasetyowati (Jurnal Sains Dasar, 2012)
Solar cells based on titania was developed continually to reach better performance. To improve the efficiency, titania layer was inserted by Fe metal. Insertion of Fe metal on TiO2 layer has been done by electroplating method with various electroplating voltage and electroplating time duration. Absorption capabilitis of TiO2 was identified by using UV-Vis spectrometer. Morphological structure and composition of materials on TiO2 layer before and after electroplating was identified by SEM (Scanning Electron Microscopy). Structure of solar cells that have been made were characterized by using the I-V meter to determine the performance of solar cells. Solar cell with TiO2 active layer without  insertion of  Fe only has a solar to electric energy conversion efficiency  0.001%. While solar cells with TiO2 active layer which was inserted Fe have a solar to electric energy conversion efficiency 0.2%. Insertion of Fe on the TiO2 layer formed metal contact layer as a path for electrons to transfer more quickly to the electrode (ITO).